COVID-19 vaccination in patients on biologic or targeted-synthetic disease modifying anti-rheumatic drug therapy: A multi center real-world data - Yildirim, Tuba Demirci; Akleylek, Cansu; Yildirim, Derya; Cinakli, Haluk; Hakbilen, Selda; Coskun, Belkis Nihan; Onen, Fatos (Wolters Kluwer Medknow Publications, 2025)
Objective:To assess the effectiveness of COVID-19 vaccination in patients with rheumatic diseases undergoing biologic (bDMARDs) or targeted-synthetic disease-modifying anti-rheumatic drugs (tsDMARDs). Methods:This cross-sectional study was conducted at ten rheumatology clinics in Turkey between May 1, 2021, and October 30, 2022. Patients with rheumatic diseases on bDMARD or tsDMARD therapy who received at least two doses of an mRNA or inactivated SARS-CoV-2 vaccine were included. After vaccination, COVID-19 infection rates, adverse events, and rheumatic disease flares were recorded. Data were collected via face-to-face or telephone interviews. Results:A total of 963 participants were included in the final analysis; 44% were male, and the median age was 49 years. The most frequently observed rheumatic diseases were ankylosing spondylitis and rheumatoid arthritis, accounting for 37.2% and 32.6% of cases, respectively. Adalimumab (19.2%) and infliximab (17.8%) were the most commonly used bDMARDs. Of the participants, 634 (65.9%) received an inactivated vaccine (CoronaVac) and 329 (34.1%) an mRNA vaccine (BioNTech). A total of 502 (52.1%) patients received a booster dose. Following the first, second, and third vaccine doses, adverse event rates were 19.9%, 15.9%, and 26.7%, respectively. Forty-two (4.4%) patients experienced a disease flare within six months after their first vaccination dose. COVID-19 infection occurred in 79 participants (8.2%) after two vaccine doses; most cases were symptomatic but did not require hospitalization. The COVID-19 infection rate was lower in participants who received a booster dose than those who did not (3.4% vs. 8.2%, P<0.001). Conclusions:Our study indicates that both mRNA and inactivated SARS-CoV-2 vaccines are effective in preventing severe COVID-19 outcomes, with an acceptable rate of adverse events and disease flares among patients with rheumatic diseases on bDMARD or tsDMARD therapy.
Keywords: bDMARDs; Rheumatic diseases; Vaccination; COVID-19; Adverse events; Flares